2012
DOI: 10.1158/0008-5472.sabcs12-p6-10-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-10-01: A randomized phase 2 study of the antibody-drug conjugate CDX-011 in advanced GPNMB-overexpressing breast cancer: The EMERGE study

Abstract: Background: GPNMB is an internalizable transmembrane glycoprotein overexpressed in multiple tumor types, including breast cancer (BC). GPNMB promotes BC metastases in a murine model and is a poor prognostic marker in patients (pts) (Rose 2010). CDX-011 (glembatumumab vedotin) is a fully human GPNMB-specific monoclonal antibody conjugated to the potent cellular toxin MMAE via a protease-sensitive peptide linker, designed to cleave upon cellular internalization. In Phase I/II studies of CDX-011 in BC (n = 42), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In these studies, development of a skin rash was one of the most common side effects experienced by melanoma (57%) and breast cancer patients treated with CDX-011 (48%, 47%) 103,104,107. This finding was of great interest, given that GPNMB is expressed in the skin 65,67.…”
Section: Gpnmb As a Therapeutic Targetmentioning
confidence: 97%
See 2 more Smart Citations
“…In these studies, development of a skin rash was one of the most common side effects experienced by melanoma (57%) and breast cancer patients treated with CDX-011 (48%, 47%) 103,104,107. This finding was of great interest, given that GPNMB is expressed in the skin 65,67.…”
Section: Gpnmb As a Therapeutic Targetmentioning
confidence: 97%
“…Interestingly, melanoma patients who experienced rash within their first cycle of treatment also had significantly longer PFS than CDX-011-treated patients who didn’t develop rash (4.8 versus 1.2 months; P < 0.001), suggesting that rash may be an early indicator of a patient’s ability to tolerate and respond to the drug 103. Additional side effects in the EMERGE study that were worsened in patients treated with CDX-011 compared to IC include other dermatological conditions such as alopecia (hair loss) and pruritus (itch) as well as peripheral neuropathy and vomiting 107. However, patients undergoing CDX-011 therapy witnessed a reduction in hematologic side effects such as neutropenia, leucopenia, and thrombocytopenia.…”
Section: Gpnmb As a Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase IIb study showed that in patients with high GPNMB expression, CDX-011 therapy was associated with median OS was 10.0 months compared with 5.5 months with chemotherapy (p = 0.003). Fatigue, rash, nausea, peripheral sensory neuropathy, and neutropenia were the most frequent adverse events [45]. CDX-011 is now being compared with capecitabine monotherapy in a randomized clinical trial for patients with metastatic TNBC.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…Upon binding to GPNMB and internalization of the antibody‐drug conjugate, the drug is cleaved, and microtubule inhibition leads to cell cycle arrest and apoptosis . Glembatumumab vedotin, in early phase clinical trials, has led to increased progression free survival in patients with melanoma and breast cancer …”
Section: Introductionmentioning
confidence: 99%